2016
DOI: 10.1042/bcj20160385
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin impairs cardiomyocyte viability by suppressing transcription factor EB expression and disrupting autophagy

Abstract: Doxorubicin (DOX) is an effective anti-cancer agent. However, DOX treatment increases patient susceptibility to dilated cardiomyopathy. DOX predisposes cardiomyocytes to insult by suppressing mitochondrial energy metabolism, altering calcium flux, and disrupting proteolysis and proteostasis. Prior studies have assessed the role of macroautophagy in DOX cardiotoxicity; however, limited studies have examined whether DOX mediates cardiac injury through dysfunctions in inter- and/or intra-lysosomal signaling event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 66 publications
9
69
0
Order By: Relevance
“…For instance, cardiac glucolipotoxicity in obesity and diabetes has been linked to diminished TFEB and autophagic flux in cardiomyocytes [48]. Disrupting the ALP through impairing lysosome acidification and repressing TFEB signaling was recently reported to contribute to doxorubicin cardiotoxicity [49, 50]. TFEB-mediated transactivation of ALP machinery was proposed to mediate the protection by intermittent fasting against myocardial ischemia-reperfusion injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cardiac glucolipotoxicity in obesity and diabetes has been linked to diminished TFEB and autophagic flux in cardiomyocytes [48]. Disrupting the ALP through impairing lysosome acidification and repressing TFEB signaling was recently reported to contribute to doxorubicin cardiotoxicity [49, 50]. TFEB-mediated transactivation of ALP machinery was proposed to mediate the protection by intermittent fasting against myocardial ischemia-reperfusion injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular calcium-tolerant myocytes were prepared by a previously described procedure 52 . Cardiomyocytes were plated on laminin coated plates at a final cell density of 40–70 × 10 3 cells/plate, incubated at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence-based detection of ‘dots’ (autophagosomes) containing either endogenous LC3-II, or overexpressed GFP-LC3 also pointed to the upregulation of autophagosome formation or accumulation, in in vitro and in vivo studies [11, 68, 77, 79, 82, 85]. In some models, however, decreased relative levels of lipidated LC3-II in response to Dox were reported [8688]. Dox induced up-regulation of Beclin-1 and Atg-5 has been corroborated by several studies [68, 77, 80].…”
Section: Dox and The Autophagy Processmentioning
confidence: 99%
“…There is an emerging consensus, strengthened by recent studies, that Dox inhibits autophagic flux, by inhibiting lysosomal biogenesis and/or lysosomal function [72, 75, 88, 105, 106]. Bartlett and colleagues demonstrated that Dox decreases expression of TFEB (transcription factor EB) which regulates the expression of genes related to autophagy and lysosomal biogenesis [88].…”
Section: Dox and The Autophagy Processmentioning
confidence: 99%